Office environment and workers’ productivity: empirical evidence of government workers in Kota Belud, Sabah, Malaysia / Leviana Andrew ... [et al.] - Andrew, Leviana; Mathew, Darrold Hansen; Mohd Zamri, Norfarahzila; Abdul Latiff, Siti Fatimah; Mohd Hamdi, Shahera Shaziah (2022)
Office environment and its relationship with worker productivity is an area of interest for office administrators to set up an office. While most studies proved that there was a significant correlation between the two variables, others presented inconclusive findings. This study explored the relationship between office environment and productivity among the government workers in Kota Belud, Sabah. It focused on four variables of office environment which include furniture, temperature, noise, and lighting. The population of this study are employees in a government institution in Kota Belud, Sabah. This quantitative study employed questionnaire distribution to 115 government employees through convenience sampling method. The findings indicated that the government workers in Kota Belud agreed that office environment does affect their work productivity. All variables of office environment were significant and positively correlated with workers’ productivity. Furthermore, the research reflected that these workers would pay more attention to the quality of office environment aspects for better workers’ productivity and job performance.